Impact of biologic therapy on blood cell indices and exacerbation risk in severe asthma: predictive value of the neutrophil-to-eosinophil ratio - Al-Ahmad, Mona; Ali, Asmaa; Talat, Wafaa (Frontiers in Allergy, 2025)
BackgroundAlthough biologic therapies have transformed the management of severe asthma, reliable blood-based markers to measure treatment response and predict residual exacerbation risk remain limited. The aim of this study was evaluating routine hematologic indices as predictors of disease control and exacerbations after biologic therapy.MethodsA cohort study included 107 patients with severe asthma were assessed before and after one year of initiating biologics. Asthma control was measured with the Asthma Control Test (ACT) and Asthma Control Questionnaire (ACQ-6); exacerbations were prospectively recorded. Complete blood counts were obtained at both time-points.Resultspatients with severe asthma were predominantly middle-aged, obese, non-smoking women with poorly controlled asthma and elevated eosinophil counts. Biologic therapy resulted in a significant reduction in median blood eosinophil count, halving it from 480 to 240 cells/µl (p < 0.001). Smaller but statistically significant decreases were also observed in total leukocyte count and neutrophil count (both p = 0.02), leading to a marked increase in the neutrophil-to-eosinophil ratio (NER, p < 0.001). Post-treatment, higher neutrophil counts and NER correlated with poorer asthma control, while elevated neutrophils, monocytes, and NER were significantly associated with exacerbations. Logistic regression confirmed monocytes (OR 1.03, P = 0.01) and NER (OR 1.07, P = 0.04) as independent predictors of exacerbation, with ROC analysis showing their significant discriminative ability (AUC 0.64-0.66). Depending on the clinical objective to rule out or confirm exacerbation risk, specific cutoffs for NER (>3.97) and monocytes (>435/µl) offered high sensitivity (∼92%), or high cutoffs for NER (>50.65) and monocytes (>755/µl) offered high specificity (∼91%).ConclusionBiologic therapy significantly reduced eosinophils and altered NER in severe asthma. Prominently, elevated post-treatment neutrophils, monocytes, and particularly a higher NER, were significant predictors of poorer asthma control and increased exacerbation risk, offering clinically useful biomarkers for personalized management.